Robotic-Assisted Mini-Gastric By-Pass for Diabetes in Children: A First Case Report and Review of the Literature - Cag, Murat; Ozdemir, Yesim; Civilibal, Mahmut; Korkmaz, Askin Ali; Silay, Mesrur Selcuk (International Journal of Innovative Research in Medical Science, 2022)
Objectives: Obesity is one of the most common diseases of children across the globe with repercussion because of comorbidities like diabetes for the future followed by premature deaths. We aimed to report the world first case of robotic-assisted mini-gastric by-pass in 15 years old boy to treat diabetes and obesity. Surgical technique and review of the literature has been presented. Patient and Methods: Fifteen years old male with Body Mass Index (BMI) 58.6 at 125 percentile, and the patient was followed by dietetic counseling and with increasing metformin dosage treatment because of insulin resistance in his country. After 3 years of follow up the patient’s treatment was not successful and therefore the family addressed to our obesity council. Our genetic consultant assured the boy doesn’t have MC4R mutation. Other endocrinologic comorbidities was evaluated by a pediatrician specialist on obesity and referred to a pediatric endocrinologist. The Type 2 diabetes was diagnosed. Robotic assisted mini-gastric by-pass was planned. Under general anesthesia five instrument ports were placed. Then the robot was docked. The stomach was divided with stapler at the junction of the body and antrum, at a location where the jejunal loop can be brought up comfortably. The jejunal loop is brought up antecolic, and the stapler is used to anatomose the stomach and the small bowel at this point. The distal end of the gastric tube is anastomosed to the side of the small bowel. Methylene blue was given to ensure there was no leakage at the anastomosis and the stapling sites. The antidiabetics were stopped by the operation. The patient was followed for a month with a normalization of blood glucose levels and without medical nor surgical complication. Results: Operative time was 105 minutes. No intraoperative complication was encountered. The patient started walking 6 hours postoperatively. The first postoperative day glucose levels were within the normal limits. Oral contrast CT demonstrated neither leakage nor obstruction on the first day. Patient started oral intake within 24 hours and was discharged in 3 days without any postoperative complication. After 1 month of follow up we didn`t saw any perturbation on blood glucose level. Conclusion: Robotic-assisted mini gastric by-pass is feasible in diabetic children. The main postoperative advantages are early recovery, less pain and better cosmesis with a easily revisable and reversible operation.